Considerations about cryptosporidiosis - Bresciani, Katia Denise Saraiva [UNESP]; Gomes, Jancarlo Ferreira; Coelho, Willian Marinho Dourado [UNESP]; Inácio, Sandra Valéria [UNESP]; De Matos, Lucas Vinicius Shigaki [UNESP]; Oliveira, Bruno César Miranda [UNESP]; Pierucci, Julia Cestari [UNESP]; Falcão, Alexandre Xavier (My University, 2017)
Cryptosporidiosis is a disease caused by an intestinal protozoan of the genus Cryptosporidium, which can affect humans and several animal species and parasitize preferentially epithelial cells of small and large intestine s. Diarrhea is the most common symptom in immunodeficient and immunocompetent hosts. In this chapter, we will discuss general aspects of this important disease.
Keywords: Cryptosporidium; Parasite; Protozoa